Relationship between temperament, character and the autistic trait in parents of children with autistic spectrum disorder. (August 2015) - Kadak, Muhammed Tayyib; Demirel, Ömer Faruk; Gökalp, Burcu; Erdoğdu, Zeynep; Demirel, Ayşegül
Abstract Objective. Previous studies have revealed distinct features of autism, with higher harm avoidance and lower reward dependence and novelty seeking. It is assumed that high harm avoidance, and low novelty seeking, reward dependence, cooperativeness, and self-directedness are related with the broad autism phenotype, as seen in autistic individuals. Method. This study examined the association between the Temperament and Character Inventory (TCI) and the Autism Spectrum Quotient (AQ), in parents of children with ASD. Result. There was significant correlation between total AQ and total harm avoidance, cooperativeness, and self-directedness (p < 0.05). In the stepwise analysis, self-directedness and education emerged significantly (F(2, 67) = 19.71, p < .005). This model modestly explained 35% of variance (Adjusted R2 = .350). Conclusion. Our findings suggest that self-directedness may be an autistic trait.